Método de dessalga de "jerked beef" como procedimento para garantir inocuidade - Ana Carolina Barbosa Duarte (2012)
The jerked beef is a typical Brazilian product made from beef and is slowly being discovered by consumers nationwide. It is an industrialized meat product, made of salted beef, cured and dried. The desalting operation is a necessary step for preparing the base plates of that ingredient, which can be critical, since it allows the development of pathogenic microorganisms by increasing the water activity. Currently, there isnt a provision in the legislation nationwide to guide people on the desalting procedure of dried meat. The aim of this work was to study three desalting methods to establish which is the most appropriate and safest. Three treatments were used: desalting at room temperature (DA), desalting chilled (DR) and desalting to room temperature, followed by cooking (DC). The microbiological and physical-chemical analysis were performed at time zero and after 12 and 24hours after desalting. In 24 hours time, DC showed the lowest scores (p <0.05) of mesophilic aerobic viable strict and facultative microrganisms (2.07 ± 0.31 log CFU/g), Staphylococcus aureus (<2.00 ± 0.00 log CFU/g), total coliforms (<3.0 MPN / g), fecal coliforms (<3.0 MPN / g) and absence of Salmonella sp. Regarding physical-chemical analysis, DC treatment showed (p <0.05) lower moisture (58.99 ± 2.10 g/100 g), ash (2.64 ± 0.53 g/100g) and chloride (1,90 ± 0.17 g/100g) contents and higher protein content (26.75 ± 1.90 g/100g). No significant differences were observed in lipids content and water activity. Desalting at room temperature for 24 hours followed by boiling, had a better nutritional profile and is a safe procedure, which may be used in food services for preparing dishes based on jerked beef as an ingredient.